A novel efficient single-phase dual-emission phosphor with high resemblance to the photosynthetic spectrum of chlorophyll A and B; Journal of Materials Chemistry C; Vol. 8, iss. 18 - Fang Shuangqiang; Lang Tianchun; Khan (Han) Tao; Cai Mingsheng; Cao Shixiu; Peng Lingling; Bitao Liu; Zhong Yang; Yakovlev A. N. Aleksey Nikolaevich; Korepanov V. I. Vladimir Ivanovich (2020, 2020)
Title screen